2021
DOI: 10.1038/s41467-021-22041-2
|View full text |Cite|
|
Sign up to set email alerts
|

Aberrant TGF-β1 signaling activation by MAF underlies pathological lens growth in high myopia

Abstract: High myopia is a leading cause of blindness worldwide. Myopia progression may lead to pathological changes of lens and affect the outcome of lens surgery, but the underlying mechanism remains unclear. Here, we find an increased lens size in highly myopic eyes associated with up-regulation of β/γ-crystallin expressions. Similar findings are replicated in two independent mouse models of high myopia. Mechanistic studies show that the transcription factor MAF plays an essential role in up-regulating β/γ-crystallin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…Considering the impact of lens in refractive system among elder individuals, we used axial length in definition of high myopia referring to previously conducted studies. [21][22][23][24][25] High myopia was defined as AL≥26 mm. Age and sex matched controls were recruited from hospital employees and volunteers from the public.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the impact of lens in refractive system among elder individuals, we used axial length in definition of high myopia referring to previously conducted studies. [21][22][23][24][25] High myopia was defined as AL≥26 mm. Age and sex matched controls were recruited from hospital employees and volunteers from the public.…”
Section: Methodsmentioning
confidence: 99%
“…As the crystalline lens were the core refracting medium of the eye, 27 thus it may be a critical step to understand the changes of the crystalline lens to prevent HM. Previous studies suggested no difference in lens thickness 28–30 but larger in lens diameter size 12 in highly myopic eyes compared to emmetropic eyes. In our present study, various energy metabolic-related gene sets were enriched in the lens epithelia of HM eyes, which indicated more lens content is produced in HM eyes.…”
Section: Discussionmentioning
confidence: 88%
“…The HM-related data set GSE136701 12 was downloaded from Gene Expression Omnibus ( https://www.ncbi.nlm.nih.gov/geo/ ). GSE136701 contains gene expression profiles based on the GPL570 of lens epithelia from three human highly myopic eyes and three emmetropic control eyes and was based on the GPL570 platform.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As specified by ISO 11979-3, premarketing testing of the mechanical properties of IOLs intended for capsular bag implantation that determine angle of contact in addition to other endpoints is done with placement of the IOL in a single-size (10 mm) compression well [14]. However, it is well known that the anatomy and capsular bag size vary among eyes, increasing with increasing axial length [15][16][17][18]. Furthermore, as a result of capsular bag fibrosis, capsular bag size decreases postoperatively and in an unpredictable manner [17].…”
Section: Introductionmentioning
confidence: 99%